LATE DEVONIAN-CARBONIFEROUS CONODONTS FROM EASTERN IRAN (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1999)
Conodont data from acid-leaching 110 samples from two Late Devonian-Carboniferous areas in the Shotori Range (Tabas region) of eastern Iran are presented. At Howz-e-Dorah, a section (88 samples) commencing high in the Bahram Formation (Givetian-early Frasnian) extended through the Shishtu Formation (Frasnian, Early hassi Zone or older, to latest Tournaisian, anchoralis-latus Zone) and the Sardar Formation (earliest Visean, texanus Zone, to late Namurian, sinuatus-corrugatus-sulcatus Zone) and into the Jamal Formation (Permian). Four less exhaustively sampled sections (22 samples) show the Kale Sardar area to be tectonically more complicated than the Howz-e-Dorah area. Useful marker horizons in the Howz-e-Dorah section, well constrained by conodont data, are: the early Frasnian (no older than Early hassi Zone) biostromal beds of the Shishtu Formation, an early Famennian (Late triangularis to Early crepida) interval of oolitic limestone, a cyclothem sequence straddling the Early Carboniferous-Late Carboniferous boundary, and an Early Permian interval of siliceous sand ("the white quartzite" of previous authors). Additionally, several iron-rich horizons, readily traceable from locality to locality, are well constrained by conodont ages. Eighty-five conodont species/subspecies are documented representing 24 genera.. Two new species, Polygnathus capollocki and Polygnathus ratebi and one new subspecies, Icriodus alternatus mawsonae are described.